On the plasma rotation in a straight magnetized filter of a pulsed vacuum arc - Giuliani, Leandro Estanislao (2007)
In vacuum arcs of interest for ion deposition, in which a magnetic filter is used, significant plasma rotation about the filter axis can develop. In the present work we present experimental evidence and simplified models to interpret relatively fast rotation of plasma generated in a pulsed vacuum arc with a straight magnetic filter and with a magnetic field strength in the range 52–430 G. The plasma rotation is produced in the first part of the filter (the driving region) where either the expanding or the contracting plasma encounters a mainly axial magnetic field. In the next part of the filter (the rotation region) a quasi-equilibrium is achieved and the plasma does not evolve further significantly. A rigid-rotor type of equilibrium is considered to model the rotation region, with experimentally obtained parameters, and a simple model is employed in the driving region to quantify the magnitude of the plasma rotation. It is found that at the quoted values of the magnetic field plasma rotation is an essential constituent to consider in any self-consistent theoretical model for the plasma inside the filter.